2021
DOI: 10.3390/s21237995
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Running Cadence and Stance Time Derived from Instrumented Wireless Earbuds

Abstract: Instrumented earbuds equipped with accelerometers were developed in response to limitations of currently used running wearables regarding sensor location and feedback delivery. The aim of this study was to assess test–retest reliability, face validity and concurrent validity for cadence and stance time in running. Participants wore an instrumented earbud (new method) while running on a treadmill with embedded force-plates (well-established method). They ran at a range of running speeds and performed several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
4
7
1
Order By: Relevance
“…With slow running in place, the mean bias was less than 1 step/min (between −0.4 and 0.2 steps/min) for all four devices-lowest (0.1 steps/min) for the Qualisys motion capture system and highest (−0.4 steps/min) for the Garmin Running Pod. In their investigation of the validity of measuring running cadence (step rate) with earbuds, Nijs et al [20] observed a maximal mean cadence of 181 steps/min, which is comparable to our slow rate of running in place (179 steps/min). In their study, the mean bias between the values provided by the force plates and the earbuds was 1.3 steps/min, which is higher than the mean bias for any of the devices evaluated here.…”
Section: Discussionsupporting
confidence: 80%
“…With slow running in place, the mean bias was less than 1 step/min (between −0.4 and 0.2 steps/min) for all four devices-lowest (0.1 steps/min) for the Qualisys motion capture system and highest (−0.4 steps/min) for the Garmin Running Pod. In their investigation of the validity of measuring running cadence (step rate) with earbuds, Nijs et al [20] observed a maximal mean cadence of 181 steps/min, which is comparable to our slow rate of running in place (179 steps/min). In their study, the mean bias between the values provided by the force plates and the earbuds was 1.3 steps/min, which is higher than the mean bias for any of the devices evaluated here.…”
Section: Discussionsupporting
confidence: 80%
“…Eight studies combined controlled and self-selected speeds [ 35 , 62 , 76 , 116 , 118 , 127 , 132 , 135 ]. For example, Giandolini et al examined participants at 10, 12, 14 (female) and 16 km/h (male), maximum aerobic speed and participant’s preferred speed [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Self-selected speeds were used in 21 studies, with a range from jogging [ 136 ] to maximum effort/sprint [ 86 , 99 , 100 , 102 , 104 , 105 , 129 , 133 ]. An additional five studies combined controlled and self-selected speeds [ 62 , 76 , 116 , 127 , 135 ]. One study did not comment on the treadmill speeds used [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations